Metode Penilaian Startup: Systematic Literature Review atas Pendekatan Finansial dan Non-Finansial - Irsyad Kamal (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Determining startup valuation is an important aspect of investment decision-making and business strategy, but faces challenges such as limited financial data and market uncertainty. This study used Systematic Literature Review (SLR) to analyze 169 articles from Scopus (2015-2025), and selected 17 studies to examine startup valuation models. The results show that financial approaches, such as DCF and VCM, are more effective for startups with stable revenue, but less relevant for early-stage startups. On the other hand, non-financial approaches, such as Berkus and Scorecard Method, are more widely used for early-stage startups that do not yet have a strong financial track record. Technological innovations such as AI and machine learning are also being applied to improve valuation accuracy. This research suggests that a combination of financial and non-financial approaches is more effective and highlights the research gap in the integration of both approaches, as well as the valuation of blockchain and digital asset-based startups.